Ca2+-Dependent Processes of Innate Immunity in IBD - Francesco Palestra; Gina Memoli; Annagioia Ventrici; Marialuisa Trocchia; Mariarosaria Galdiero; Gilda Varricchi; Stefania Loffredo (Cells, 2024)
IBD is an uncontrolled inflammatory condition of the gastrointestinal tract, which mainly manifests in two forms: ulcerative colitis (UC) and Crohn’s disease (CD). The pathogenesis of IBD appears to be associated with an abnormal response of innate and adaptive immune cells. Innate immunity cells, such as macrophages, mast cells, and granulocytes, can produce proinflammatory (e.g., TNF-α) and oxidative stress (ROS) mediators promoting intestinal damage, and their abnormal responses can induce an imbalance in adaptive immunity, leading to the production of inflammatory cytokines that increase innate immune damage, abate intestinal barrier functions, and aggravate inflammation. Considering that Ca2+ signalling plays a key role in a plethora of cellular functions, this review has the purpose of deepening the potential Ca2+ involvement in IBD pathogenesis.